Knowledge of Family Planning among Nursing Students at a Private Institute Karachi : Family Planning among Nursing Students - Khan, Jehangir; Ali, Mahboob; Bibi, Afsha; Maqsad, Sakina; Tehseen, Saima; Shah, Sadiq Hussain; Javed, Rukhsana Samson; Naveed, Sabir; Zeeshan, Salima (Pakistan Journal of Health Sciences, 2024)
Family planning (FP) is defined as the whole effort made by a couple to prevent pregnancy and to create some space among their children. FP helps in avoiding undesirable pregnancies thus promote maternal and child health. Objective: To evaluate the knowledge of FP among nursing students. Methods: A descriptive cross-sectional study was used at Horizon School of Nursing with a total of 80 students selected through purposive sampling technique. SPSS version 26 was used for data analysis. Results: Study results showed that 45% of the students were in age group 20-30 years, 61.2% were female and if we talk about spouse education status all of them were literate, most of the respondent’s monthly income was between 30,000-50,000 PKR, 47.5% were having no children, 40% having 1-2 children, 50% of them wished to have 1-2 children, most of them (48.8%) had 1-2 years interval between their children, majority of the respondents (88.8%) had heard of FP, the source of information regarding FP mostly (56.2%) were hospitals, availability of FP services known by respondents were private hospitals (83.8%) and methods of FP known by the students mostly (42.5%) were condoms. Conclusions: The study showed that only 42.5% of the students knew the condom method of FP, 23.7% withdrawal methods, 20% oral contraceptive pills, and a very low percentage of other methods of FP which need to be enhanced by conducting seminars and other awareness programs in nursing schools and colleges.